Substantiation of Indicators and Formalization of Integral Index of Strategic Analysis of Enterprises - Khorunzhak N. (Modern Economics, 2019)
A characteristic feature of the current economic environment in which Ukrainian businesses operate is a significant increase in competition, an increase in requirements for product quality (works, services), an emphasis on socialization of production, resource conservation and efficiency. It is important for enterprises to have adequate indicators of assessing the impact on their activities of external and internal factors in order to function effectively in such environment. Such information can be obtained by using the tools and methods of strategic analysis. The article is devoted to topical issues of strategic analysis development and improvement of its indicators.